Pengaruh Aras Starter Lactobacillus sp Terhadap Performa Mikrobiologi Silase Ikan Dilihat Dari Total Bakteri, Bakteri Asam Laktat Dan Fungi - Sri Sumarsih; B. Sulistiyanto; H.S. Adi; C.S. Utama (JURNAL KESEHATAN, 2010)
The aim of the research was to evaluate the effect of addition starter Lactobacillus sp on microbiologic performances was been seen from total bacterial, lactic acid bacteria and fungal of fish iilage. The researih material were fish waste (ikan rucah), rice bran, Lactobacillus sp, fisiologic NaCl, NA (Nutrient Agar), MRS (de Man, Rogosa, and Sharpe) Broth, and SGA (Saboroud Glucose Agar). The completely randomized design was been used on this research with 5 treaments and 3 replications. The treatments were C0 (level starter 07o), Cl (level starter2Yo), C2 (level starter 4o/o), C3 (level starter 60/o) and C4 (level starter 8%). fheparameters were total bacterial, lactic acid bacteria and fungal of fish silage. The results showed that addition of starter Lactobacillus sp has no affected to total bacterial and fungal of fish silage. The addition increased(p<0,01) total lactic acid bacteria of fish silage. The conclusion was addition of starter Lactobacillus rp wir been stored during 2 weeks no affect total bacteria and fungi of fish silage. Addition of 4% level itarterLactobacillus sp increased total lactic acid bacteria offish silage.Keyword ; stafter Lactobacillus sp, fish silage, total bacteria, total fungi